Stability of a fractional advection–diffusion system with conformable derivative. (November 2022) - Arfaoui, Hassen; Ben Makhlouf, Abdellatif
Abstract: This paper investigates the stability of fractional advection–diffusion system with conformable derivative in infinite time interval. We have established new exponential stability results for a such system in different Hilbert spaces. Then, thanks to numerical methods for solving systems with conformable derivative, we were able to justify numerically the theoretical results obtained.